Mesomorphic, structural, electro-optic and dynamic properties of lactic acid derivative and its selectively deuterated isotopomers by means of electro-optics, SAXS, 2H-NMR and neutron spin-echo spectroscopy. Issue 13 (20th October 2020) - Bubnov, Alexej; Cifelli, Mario; Cigl, Martin; Fouquet, Peter; Hamplova, Vera; Domenici, Valentina
ABSTRACT: In this work, we present the synthesis of two analogues of a lactic acid derivative selectively deuterated on phenyl and biphenyl moieties together with a detailed investigation of their properties within the Twist Grain Boundary smectic A* (TGBA*), the ferroelectric Smectic C* (SmC*) and the crystal E phases. The main structural features of the two liquid crystalline phases, namely TGBA* and SmC* phases, were determined by polarising optical microscopy, differential scanning calorimetry, electro-optical techniques, Small Angle X-ray Scattering (SAXS) and 2 H Nuclear Magnetic Resonance ( 2 H NMR) measurements. Preliminary results from Neutron Spin-Echo (NSE) spectroscopy, a technique rarely applied to study chiral liquid crystalline materials, are reported. The effect of the external magnetic field on the supramolecular structure of the ferroelectric phase was studied by means of 2 H-NMR experiments under different external magnetic fields. The supramolecular and orientational ordering properties of this ferroelectric lactic acid derivative and its deuterated homologues are discussed in the frame of actual knowledge in the field of ferroelectric liquid crystal materials. GRAPHICAL ABSTRACT: Scheme 1